Hubungan Dinamika Kelompok Tani Hutan dengan Tingkat Partisipasi pada Program KTH Persemaian di Desa Nagrog - Hardiyanto, Tito (Ma'soem University, 2024)
This research aims to examine the dynamics of forest farmer groups, the level of farmer participation, the relationship between the dynamics of forest farmer groups and the level of farmer participation. This research uses a case study method at KTH Giri Jaya in Nagrog Village, Cicalengka District, Bandung Regency. The technique for taking respondents was the census method with the unit of analysis being all members of KTH Giri Jaya, 20 farmers. The research results show that: (1) Group dynamics are in the high category; group goals, group structure, task functions, group development and maintenance, group cohesiveness, and group atmosphere are included in the high category; while group effectiveness is in the medium category, and group pressure and hidden intentions are in the low category. (2) The level of farmer participation in the KTH activity program is in the high category, with details: at the planning and evaluation stage it is in the medium category, while at the implementation and results utilization stage it is in the high category; (3) The relationship between group dynamics and the level of farmer participation in the KTH activity program shows that the higher the group dynamics, the higher the level of farmer participation which will have an impact on achieving the objectives of the KTH program activities.